PROBLEMS OF REVEALING THE LINGUISTIC AND CREATIVE IDENTITY OF THE AUTHOR’S ‘SELF’ IN NEWSPAPER DISCOURSE - Usmonova, Shahodat (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The article focuses on revealing the linguistic and creative identity of the author’s “self” in newspaper discourse. The research addresses one of the central issues in modern media linguistics: the manifestation of the author’s individuality in journalistic texts, where personal expression interacts with institutional and social norms of communication. The relevance of this study lies in the growing significance of the author’s position in shaping public opinion, constructing ideological meanings, and influencing readers through subtle linguistic and stylistic mechanisms. The purpose of the article is to analyze how the author’s “self” manifests in lexical, grammatical, and discursive structures, and to identify the creative strategies that form the linguistic image of the journalist in newspaper discourse. The novelty of the research lies in its complex approach that combines linguistic, stylistic, cognitive, and pragmatic analysis of media texts. This approach allows for a more profound understanding of how the author’s “self” functions as both a linguistic construct and a creative phenomenon within mass communication. The study reveals that the author’s individuality is encoded through metaphorical expressions, evaluative vocabulary, syntactic variation, and narrative perspective. As a result, the author’s “self” is shown to function as an important semiotic and communicative category, linking personal creativity with social discourse. The findings expand the theoretical foundations of media linguistics, discourse analysis, and stylistics, offering new perspectives for understanding the linguistic mechanisms of authorial identity in contemporary journalism.